Passion fruit (Passiflora edulis) pulp extract intake and its effect on atherogenic indices in albino rats of the Holtzman strain - Berrocal Martínez, Isabel Jesús (2020)
The research was experimental, applicative, pre- and post-test. A sample of 24 Holtzman rats, 1.5 months, weight 210 g (control group and two experimental groups, 8 rats with intake of the extract 1.5 ml and 3 ml) was taken for the study. The bioactive compounds found in the passion fruit extract were: Vitamin C (11.9 mg/100 ml), Antioxidant capacity (23531.6 u mol Trolox /100ml), Polyphenols 480.64 ±0.31 mg Ác. Gallic Acid /100 ml. The averages of atherogenic indexes I, II, III, IV after ingestion were: For the control group 3.31, 1.96, 2.31 and 1.53; for the group (1.5 ml) they were 3.14, 1.84, 2.14, 1.53 and for the group (3 ml) they were 3.52, 2.11, 2.52, 1.89, respectively. The amounts of HDL obtained after ingestion of passion fruit extract had a significant influence on the reduction of atherogenic indices, which had a positive effect, reducing cardiovascular risk factors.